Trusted management for VANETs using vehicular social Behavior - Abaid Mahdi, Muhammed (International Journal of Engineering and Technology, 2018)
Information sharing is the main task of designing the most Vehicular Ad hoc Networks (VANETs). However, determining a degree of the trustworthiness for the receiving information is still a big challenge. This paper tries to bridge social networks with vehicular networks to utilize the social relationships among vehicles in increasing the trust level of information. While vehicles are immigrating to the next smart generation, considering vehicles as social objects may be justifiable. Indeed, due to advanced technologies vehicles can wirelessly contact with each other. Moreover, a level of intelligence those vehicles have easies the task of making decisions. The suggested method, firstly, gathers vehicles in permanent vehicular social groups (formal groups) depending on their social behavior and temporary vehicular social groups (casual groups) depending on the direction and the communication range. This grouping process assumes that vehicles in a formal group are tied with the strong social relationship. On the other hand, a casual group may consist of vehicles from different formal groups. When the source of information which is a vehicle that detects an event, shares a piece of information (the event), all members of its formal group can vote for this information. So, the trustworthiness degree of the shared information will be increased depending on the number of its votes. It means that the high number of votes the high level of trust. Eventually, each piece of information would be adopted when trusting votes of this information exceed a specific threshold. The results will discuss the main factors that affect the suggested method. Â